Role of Adenylate Cyclase 9 in the Pharmacogenomic Response to Dalcetrapib: Clinical Paradigm and Molecular Mechanisms in Precision Cardiovascular Medicine. (2nd April 2021) - Rhainds, David; Packard, Chris J.; Brodeur, Mathieu R.; Niesor, Eric J.; Sacks, Frank M.; Jukema, J. Wouter; Wright, R. Scott; Waters, David D.; Heinonen, Therese; Black, Donald M.; Laghrissi-Thode, Fouzia; Dubé, Marie-Pierre; et al.
Abstract : Following the neutral results of the dal-OUTCOMES trial, a genome-wide study identified the rs1967309 variant in the adenylate cyclase type 9 ( ADCY9 ) gene on chromosome 16 as being associated with the risk of future cardiovascular events only in subjects taking dalcetrapib, a CETP (cholesterol ester transfer protein) modulator. Homozygotes for the minor A allele (AA) were protected from recurrent cardiovascular events when treated with dalcetrapib, while homozygotes for the major G allele (GG) had increased risk. Here, we present the current state of knowledge regarding the impact of rs1967309 in ADCY9 on clinical observations and biomarkers in dalcetrapib trials and the effects of mouse ADCY9 gene inactivation on cardiovascular physiology. Finally, we present our current model of the interaction between dalcetrapib and ADCY9 gene variants in the arterial wall macrophage, based on the intracellular role of CETP in the transfer of complex lipids from endoplasmic reticulum membranes to lipid droplets. Briefly, the concept is that dalcetrapib would inhibit CETP-mediated transfer of cholesteryl esters, resulting in a progressive inhibition of cholesteryl ester synthesis and free cholesterol accumulation in the endoplasmic reticulum. Reduced ADCY9 activity, by paradoxically leading to higher cyclic AMP levels and in turn increased cellular cholesterol efflux, could impart cardiovascular protection in rs1967309 AA patients. The ongoing dal-GenE trial recruited 6145 patients with the protective AA genotype and will provide a definitive answer to whether dalcetrapib will be protective in this population.